Od Unescove konvencije o varovanju nesnovne kulturne dediščine do Registra žive kulturne dediščine na Slovenskem - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 2011)
The article presents the activities related to UNESCO's Convention for the Safeguarding of the Intangible Cultural Heritage and its ratification in Slovenia. It outlines the first reflections on the Slovene intangible heritagein the light of the convention, the preparations for its register, itsimplementation in Slovenia's Cultural Heritage Protection Act, and the workof the Coordinator of the protection of the living cultural heritage in 2009-2010, when this task was carried out by the Institute of Slovenian ethnology, SRC, SASA. The article describes the presently registered units of Slovene intangible cultural heritage, the operational guidelines of the new coordinator, and some dilemmas related to the protection and register of the intangible cultural heritage.
Keywords: Slovenci; Slovenes; nesnovna kulturna dediščina; intangible cultural heritage; živa kulturna dediščina; Unesco; living heritage; registers; registri